Treatment adherence and blood outcome among hypertensive out- in two tertiary hospitals in Sokoto, Northwestern Nigeria (2018)
Methods: Cross-sectional questionnaire-guided interview and retrospective review of medical records of 605- patients from two-tertiary healthcare institutions in Sokoto, Northwestern Nigeria. Nine-item modified Mo-risky adherence scale was used to assess medication adherence. Overall adherence score to lifestyle modifications was obtained from the total scores from 4-domains of non-pharmacological measures including cigarette smoking and alcohol cessation, salt-restriction and exercise. Patient-specific adherence education was provided at contact to resolve the knowledge gap(s). Clinical-parameters were retrieved at contact and subsequent 2-months appointment. Descriptive statistics, Chi-square and Student’s t-test were used for analysis at p < 0.05. Results: Fifty-four (8.9%) patients were adherent to medications. Forgetfulness (404; 35.2%) was the most common reason for medication non-adherence. Use of buddy/companion reminder (605, 30.2%) top the list of adherence education. Overall adherence to lifestyle modifications was 36(6.0%). Mean systolic blood pressure (SBP) at contact was 149.6 ± 22.5 versus 134.2 ± 15.8 mmHg at 2-months with a 10% reduction. There were significant associations in baseline SBP for patients with or without adherence to medication, cigarette smoking cessation, and exercise (p < 0.05). Conclusions: Overall adherence to antihypertensive medications and lifestyle modifications is suboptimal, underscoring the need for continuous patient-specific adherence education to ensure better therapeutic outcomes.